2015
DOI: 10.3390/md13042424
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-Lignin Material as a Novel Matrix for Enzyme Immobilization

Abstract: Innovative materials were made via the combination of chitin and lignin, and the immobilization of lipase from Aspergillus niger. Analysis by techniques including FTIR, XPS and 13C CP MAS NMR confirmed the effective immobilization of the enzyme on the surface of the composite support. The electrokinetic properties of the resulting systems were also determined. Results obtained from elemental analysis and by the Bradford method enabled the determination of optimum parameters for the immobilization process. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 71 publications
(73 reference statements)
2
31
0
2
Order By: Relevance
“…Lipase from Aspergillus niger has been successfully immobilized on this biopolymer–biopolymer hybrid matrix. The results of the study in question confirmed that the thermal and chemical stability of the immobilized lipase was improved …”
Section: Introductionmentioning
confidence: 66%
“…Lipase from Aspergillus niger has been successfully immobilized on this biopolymer–biopolymer hybrid matrix. The results of the study in question confirmed that the thermal and chemical stability of the immobilized lipase was improved …”
Section: Introductionmentioning
confidence: 66%
“…Activation of lipases occurs because of the amphiphilic properties of lignins, which are similar to those of synthetic surfactants . Lipase from Aspergillus niger was adsorbed on a composite material consisting of chitin and oxidized KL . The immobilization increased thermal and pH stability compared to that of native lipase.…”
Section: Entrapment Encapsulation and Adsorption Of Active Substancmentioning
confidence: 99%
“…Produksi NAG dengan menggunakan kitinase yang dihasilkan oleh Mucor circinelloides tersebut cukup tinggi sehingga merupakan salah satu cara yang dapat dilakukan untuk mengurangi produksi limbah. Namun, produksi enzim cukup sulit karena prosesnya cukup lama dan cenderung tidak stabil (Zdarta et al, 2015;Prakash et al, 2018).…”
Section: Pengantarunclassified